2002
DOI: 10.1037/0021-9010.87.5.819
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of team-efficacy, potency, and performance: Interdependence and level of analysis as moderators of observed relationships.

Abstract: Meta-analytic techniques were used to examine level of analysis and interdependence as moderators of observed relationships between task-specific team-efficacy, generalized potency, and performance. Sixty-seven empirical studies yielding 256 effect sizes were identified and meta-analyzed. Results demonstrated that relationships are moderated by level of analysis. Effect sizes were stronger at the team level (p = .39) than at the individual level (p = .20). At the team level, both team-efficacy and potency had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
796
3
21

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 839 publications
(885 citation statements)
references
References 94 publications
39
796
3
21
Order By: Relevance
“…There is previous evidence of burnout contagion (Bakker, Le Blanc, & Schaufeli, 2005) and crossover of both burnout and work engagement in work teams , where burnout and engagement are transmitted from one employee to another both consciously and unconsciously through socializing and interaction. These studies reinforce the notion that people do not perform their jobs in isolation and that team-level phenomena are of importance to individual experiences and work outcomes (e.g., Devine, Clayton, Philips, Dunford, & Melner, 1999;Gully, Incalcaterra, Joshi, & Beaubien, 2002). In line with these results, we hypothesized the following: H 2 : Employees in the same work unit will resemble each other in their experiences of burnout and work engagement (i.e.…”
Section: Shared Experiences Of Burnout and Work Engagementsupporting
confidence: 69%
“…There is previous evidence of burnout contagion (Bakker, Le Blanc, & Schaufeli, 2005) and crossover of both burnout and work engagement in work teams , where burnout and engagement are transmitted from one employee to another both consciously and unconsciously through socializing and interaction. These studies reinforce the notion that people do not perform their jobs in isolation and that team-level phenomena are of importance to individual experiences and work outcomes (e.g., Devine, Clayton, Philips, Dunford, & Melner, 1999;Gully, Incalcaterra, Joshi, & Beaubien, 2002). In line with these results, we hypothesized the following: H 2 : Employees in the same work unit will resemble each other in their experiences of burnout and work engagement (i.e.…”
Section: Shared Experiences Of Burnout and Work Engagementsupporting
confidence: 69%
“…As clearly demonstrated in the large-scale investigation undertaken by Karen Seashore Louis and colleagues for the Wallace Foundation, the development of self-efficacy and group-efficacy among the principals will support their endeavors of using the performance feedback inherent in the data sets to support improvement practices . Also as demonstrated in other studies, self-efficacy and group-efficacy are stimulated by a climate of psychological safety (Gully et al, 2002).…”
Section: Implication For Superintendent Leadership Practicementioning
confidence: 94%
“…The causal argument is that self-efficacy and collective efficacy enabled school leaders to work consistently with performance data in order to accomplish educational goals through a resilient self-belief in their capabilities to exert control over 2 Generally, self-efficacy is defined as "people's belief in their capabilities to mobilize the motivation, cognitive resources and course of action needed to exercise control over events in their lives" (Wood & Bandura, 1989, p. 364). Collective efficacy refers to a group's shared sense of efficacy related to shared tasks and goals (Gully, Incalcaterra, Joshi, & Beaubien, 2002). actual work environments.…”
Section: Figure 1: Leadership At Multiple Levelsmentioning
confidence: 99%
“…In team settings, meta-analytic reviews have demonstrated that collective efficacy has a medium to strong effect on team performance (Gully, Incalcaterra, Joshi, & Beaubien, 2002;Stajkovic, Lee, & Nyberg, 2009) and therefore we might also expect team attributions to influence team performance through changes in collective efficacy. Activation and variation in testosterone levels have also been shown to predict decisions to compete again (Mehta & Josephs, 2006), levels of cooperation (Mehta, Wuehrmann, & Josephs, 2009) and approachavoidance behaviours (Mehta, Jones, & Josephs, 2008).…”
Section: Mediating Relationshipsmentioning
confidence: 99%